Strategic Analysis of Cloud Computing Adoption in E-Commerce Digital Transformation - Chriestina Chriestina (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The objective of this research is to conduct a review of strategies of cloud computing adoption towards the digital transformation of e-commerce. A qualitative review of literature was done using 14 literature articles between 2019 and 2024 to look at how companies adopt cloud technology. The result reveals that cloud computing has strategic advantages like lower operating costs, resource agility, and better customer data analytics. But there exist some challenges such as data security, dependance on a single Cloud service provider and organizational resistance to adopt the new technology. E-commerce firms are likely to be cautious adopters and adopt hybrid and incremental approaches to reduce risks and they will also offer enhanced staff training in relation to technical skills. We also do periodical reviews of cloud service providers to maintain the stability of the system. The findings of this research provide valuable insights for businesses to plan and govern their cloud computing adoption effectively and sustainably.